2013
DOI: 10.1017/s0373463313000593
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Maritime Risk Perception and Accident Statistics in the Istanbul Straight

Abstract: The Istanbul Strait is a challenging waterway for maritime traffic due to its rough topology, moderate to severe environmental conditions, and heavy local traffic. In particular, a total of 232 maritime accidents took place there between 2000 and 2011. In this study, generic fuzzy analytic hierarchy processes were used to assess the risk perception of stakeholders in the Istanbul Strait, including ship captains, maritime pilots and Vessel Traffic Services operators. These risk perceptions were then compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 30 publications
(69 reference statements)
1
9
0
1
Order By: Relevance
“…Previous studies on maritime accidents involve a wide variety of geographical locations, including the Gulf of Finland (Mazaheri, Montewka, and Kujala 2014), Istanbul Strait (Aydogdu, 2014), the UK (Chauvin et al 2013;Bhattacharya, 2012), Greece (Tzannatos and Kokotos, 2009), Sweden (Mullai and Paulsson 2011), the heritage regions of Tubbataha and Banc d'Arguin (Heij et al 2013), the Arctic (Kum and Sahin 2015), the North Atlantic and Arctic regions (Knapp, Bijwaard, and Heij 2011), and China's Yangtze River (Zhang et al 2013;Zhang et al 2014).…”
Section: Studies Of Maritime Accidentsmentioning
confidence: 99%
“…Previous studies on maritime accidents involve a wide variety of geographical locations, including the Gulf of Finland (Mazaheri, Montewka, and Kujala 2014), Istanbul Strait (Aydogdu, 2014), the UK (Chauvin et al 2013;Bhattacharya, 2012), Greece (Tzannatos and Kokotos, 2009), Sweden (Mullai and Paulsson 2011), the heritage regions of Tubbataha and Banc d'Arguin (Heij et al 2013), the Arctic (Kum and Sahin 2015), the North Atlantic and Arctic regions (Knapp, Bijwaard, and Heij 2011), and China's Yangtze River (Zhang et al 2013;Zhang et al 2014).…”
Section: Studies Of Maritime Accidentsmentioning
confidence: 99%
“…Or and Kahraman ( 2002) conducted a survey in the Strait to elicit probable factors contributing to accidents by using Bayesian analysis and simulation modelling [26], [33], [34]. They indicated that there were remarkable increases in the number of accidents for higher transit traffic rates, denser local traffic conditions, higher percentage of longer ships and/or adverse weather conditions [35].…”
Section: Literature Review On Istanbul Straitmentioning
confidence: 99%
“…On the other hand, local and international scholars have been studying crowd evacuation methods based on meta-heuristic algorithms, achieving good results [18][19][20]. Li et al [21] proposed a genetic algorithm to optimize the design of crowd evacuation facilities.…”
Section: Introductionmentioning
confidence: 99%